1994
DOI: 10.1039/p29940000177
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of dediazoniation of arenediazonium salts with triphenylphosphine and trialkyl phosphites. Generation of cation radicals from trivalent phosphorus compounds and their reactions

Abstract: 4-Nitro-, 4-methyl-, and 4-methoxy-benzenediazonium fluoroborates are readily dediazoniated with triphenylphosphine or trialkyl phosphites (alkyl = methyl or ethyl) in alcoholic solvents at room temperature in the dark under a nitrogen atmosphere to give the corresponding arenes and the corresponding oxidation product from the phosphine or the phosphites, triphenylphosphine oxide or trialkyl phosphates, respectively, along with a small amount of biaryls. In the reaction with the phosphite, dialkyl arylphosphon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…In particular, bases (such as tertiary amines, carboxylates, or carbonates) better suited for our synthetic purposes. However, the use of N 2 or Ar is recommended because of the known sensi-as well as phosphanes [57] are known to react rapidly with diazonium salts at the β-nitrogen atom, thereby initiating tivity of organopalladium species to air. The use of trifluoroacetate salts led to a reduction in the reaction times at radical chain reactions.…”
Section: Quinone Diazidesmentioning
confidence: 99%
“…In particular, bases (such as tertiary amines, carboxylates, or carbonates) better suited for our synthetic purposes. However, the use of N 2 or Ar is recommended because of the known sensi-as well as phosphanes [57] are known to react rapidly with diazonium salts at the β-nitrogen atom, thereby initiating tivity of organopalladium species to air. The use of trifluoroacetate salts led to a reduction in the reaction times at radical chain reactions.…”
Section: Quinone Diazidesmentioning
confidence: 99%
“…[11] Surprisingly,t o date the corresponding azoammonium salts [RN 2 (NR 3 )][X] are unknown, [12] while the phosphine-diazonium Lewis adducts have been barely studied. [15,16] Flower and co-workers synthesized B,b ut only reported its 31 PNMR resonance (d 31 P{ 1 H} = 40 ppm;R= 6-naphthalen-2-ol), [17] and Wokaun and co-workers characterized C only spectroscopically (R = Cl, CN,S O 2 NH 2 ,C (O)OEt;F igure 2). [14] Later, Yasui and co-workers found that aryldiazonium tetrafluoroborates are readily dediazoniated by triphenylphosphine by single-electron transfer when mixed in alcoholic solvents at room temperature.…”
Section: Themetal-freeactivationandfunctionalizationofdinitrogenmentioning
confidence: 99%
“…[5] However, enantioselective variants of the Heck–Matsuda reaction are rare, largely because commonly employed chiral phosphine ligands are incompatible with diazonium salts. [6] …”
mentioning
confidence: 99%